Strategi Pemenangan Pasangan Drs. H. Tafta Zani, MM dan Wakilnya Drs. H. Moh. Dachirin Said, SH, M.Si Pada Pemilukada Kabupaten Demak Tahun 2011 - Aditya Ari Masadji; Susilo Utomo; Rina Martini (Journal of Politic and Government Studies, 2014)
This study analyzed the winning strategy that couples Drs. H. Tafta Zani, MM and his deputy Drs. H. Moh. Dachirin Said, SH, M.Sc. on the election Demak in 2011. Incumbent couples carried by the coalition party PKS, PPP, Golkar, and PKB was capable of winning a unanimous decision over its competitors in the election of regional heads in Demak 2011. Then , how the road concretisation strategy, campaign strategy, career strategy, mass mobilization , coalition , development and empowerment of political parties and the general strategy used pair Drs . H. Tafta Zani , MM and his deputy Drs . H. Moh . Dachirin Said , SH , M.Si in a regional election in Demak in 2011.In this study, researchers used a qualitative approach that will generate descriptive data. This research was conducted in Demak, Central Java. The data in this study was obtained through interviews, observation, and documentation. The key informant interviews were conducted by the head of the Campaign Team and some members are included in the structure of the winning team, the bearer party cadres, and the general public. While the documentation of data obtained from the secretary of the Campaign Team, the National Election Commission Demak, and BPS Demak.Winning strategy that couples Tafta Zani and Dachirin Said elections of regional heads Demak 2011 in the form of election road concretisation strategy, campaign strategy, career, mass mobilization, coalition, development and empowerment of political parties, and the public. While the campaign strategy used is researching and analyzing political opponents, polling, political alliances, promotions, campaigns on the streets, public relations, coordination and planning time for candidates, financial planning, fundraising, administration and bookkeeping, mobilization on the day of the election and planning time.The success of this winning strategy was able to win a couple of Drs. H. Tafta Zani, MM and his deputy Drs. H. Moh. Dachirin Said, SH, M.Si by a vote 377.644 votes with a percentage of 74.38 % . Couples of Tafta Zani and Dachirin Said beat of couples Sa'idah - Haryanto who get acquisition 70.849 votes with percentage of 13.95 %, couples Najib - Azzah with the acquisition of 42.644 votes with a percentage of 8.40%, and couples Purnomo – Maryono with the acquisition of 16 583 votes with percentage of 3.27 %. The victory against the backdrop of successful infrastructure development undertaken road concretisation Tafta Zani at the time served as Regent of Demak in the first period. Keywords: General Election, Regional Head Election, Winning Strategies.